Estudo funcional comparativo das co-chaperonas moleculares p23A e p23B da Hsp90 de Leishmania braziliensis - Almeida, Glessler Silva (2014)
Protein folding is essential for proteins proper biological function. Failures in this process can lead to the formation of poorly unfolded proteins and/or protein aggregates. In order to avoid this problem, the cells express a family of proteins known as molecular chaperones. The molecular chaperones are proteins that assist the correct folding of other proteins, and other important functions in the cells. The Hsp90 family is important for protein folding and it assists in preventing protein aggregation. Hsp90 is regulated by several co-chaperones, for example, p23. The p23 is a small acidic protein that regulates the ATPase activity of Hsp90. It has a structured N-terminal beta-sheet and an unstructured C-terminal domain. In addition to the regulatory role, as an inhibitor of ATPase activity of Hsp90, it also has chaperone activity in itself. Thus, the aim of this study was to investigate comparatively two p23 identified in the Leishmania braziliensis (Lbp23A and Lbp23B) genome. The proteins were expressed, purified and structurally and functionally characterized. Furthermore, functional assays such as intrinsic chaperone activity and inhibition of ATPase activity of Hsp90 L. braziliensis (LbHsp90) and identifying in vivo by western blotting were developed. The results indicate that these two proteins are structurally similar, however, demonstrated significant differences in chemical and thermal stability. The Lbp23 also differ in relation to chaperone activity and inhibition of ATPase activity of LbHsp90. The in vivo identification revealed the presence of both Lbp23 in extracts of L. braziliensis; besides suggesting possible post-translational modifications in Lbp23B. The results indicate that both Lbp23 are undoubtedly p23, since they show p23-like function and structural signs.